BIOECOLOGICAL AND MORPHOPHYSIOLOGICAL CHARACTERISTICS OF SALVIA OFFICINALIS L - Salimova Sadoqat Kamolatdin qizi; Xudayberganov Norbek Atabayevich (Journal of new century innovations, 2024)
Abstract. The bioecological and morphophysiological properties of the medicinal mavrak were studied in the soil and climate conditions of Khorezm region.